(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In this article, the protection of water sources it is almost always the best way to ensure that drinking water is safe and that in order to make water usable before use, it is preferable that the need to clean polluting sources in advance, when necessary, determine the health risk, assess the availability of alternative sources. To decide on the possibility of water supply from this water source, it is said to consider the necessary corrective measures.